2023
DOI: 10.3389/fpls.2023.1155341
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence of an Israeli isolate of Xanthomonas hortorum pv. pelargonii strain 305 and novel type III effectors identified in Xanthomonas

Abstract: Xanthomonas hortorum pv. pelargonii is the causative agent of bacterial blight in geranium ornamental plants, the most threatening bacterial disease of this plant worldwide. Xanthomonas fragariae is the causative agent of angular leaf spot in strawberries, where it poses a significant threat to the strawberry industry. Both pathogens rely on the type III secretion system and the translocation of effector proteins into the plant cells for their pathogenicity. Effectidor is a freely available web server we have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Furthermore, transcriptome analysis of Xaf in strawberries revealed that T3Es can be functional in Xaf during the pathogenesis process (Gétaz et al, 2020; Puławska et al, 2020). Recently, 47 T3Es were mined based on a machine-learning method, and two novel Xaf T3Es, XopBG and XopBF, were translocated and elicited hypersensitive reaction (HR) on pepper leaves, revealed its possible pathogenic role in Xaf Fap21 (Wagner et al, 2023). So far, there is still very limited knowledge on the in-depth interaction mechanism between Xaf T3Es and strawberries, which may be attributed to the difficulties in overcoming technological hurdles associated with Xaf genetic editing and the absence of resistant materials (Vandroemme et al, 2013; Maas et al, 2000, 2002; Roach et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, transcriptome analysis of Xaf in strawberries revealed that T3Es can be functional in Xaf during the pathogenesis process (Gétaz et al, 2020; Puławska et al, 2020). Recently, 47 T3Es were mined based on a machine-learning method, and two novel Xaf T3Es, XopBG and XopBF, were translocated and elicited hypersensitive reaction (HR) on pepper leaves, revealed its possible pathogenic role in Xaf Fap21 (Wagner et al, 2023). So far, there is still very limited knowledge on the in-depth interaction mechanism between Xaf T3Es and strawberries, which may be attributed to the difficulties in overcoming technological hurdles associated with Xaf genetic editing and the absence of resistant materials (Vandroemme et al, 2013; Maas et al, 2000, 2002; Roach et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Pathogens often deploy the highly conserved type-III secretion system (T3SS) to transfer virulence proteins, known as type III effectors (T3Es), into eukaryotic host cells to invade their hosts and influence plant responses to favor infection (Büttner & Bonas, 2003; Dangl & Jones, 2019; Duxbury et al, 2016). There are 25 T3Es identified in the draft genome of Xaf strain LMG25863 (Vandroemme et al, 2013), 47 T3Es in Xaf strain Fap21 identified by machine-learning (Wagner et al, 2023), 33 T3Es in Xaf strain YL19 in our previous study based on homolog blast (Wei et al, 2022), yet most of these T3Es remain functionally uncharacterized. Finding the proteins that these putative pathogenic effectors target on their host will be essential to assigning roles to them.…”
Section: Introductionmentioning
confidence: 99%